2020
DOI: 10.1016/j.ceramint.2019.09.219
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and properties of zirconia/hydroxyapatite composite scaffold based on digital light processing

Abstract: Lida (2019) Fabrication and properties of zirconia/hydroxyapatite composite scaffold based on digital light processing. Ceramics International.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(53 citation statements)
references
References 45 publications
1
52
0
Order By: Relevance
“…e pore size and strut size of the sintered sca olds were about 650 μm and 450 μm, respectively, as shown in Figure 1. In general, porous bone sca olds was able to provide a favorable microenvironment for cell into-growth [28,29].…”
Section: Preparation Of Plla/cnts Composite Sca Oldmentioning
confidence: 99%
“…e pore size and strut size of the sintered sca olds were about 650 μm and 450 μm, respectively, as shown in Figure 1. In general, porous bone sca olds was able to provide a favorable microenvironment for cell into-growth [28,29].…”
Section: Preparation Of Plla/cnts Composite Sca Oldmentioning
confidence: 99%
“…As one of the three elements of bone tissue engineering, artificial bone scaffold plays an extremely important role in bone repair process [1,2]. Ideally, scaffolds should have high porosities with open pore structure, over which cells can rapidly grow and develop into tissues that are viable [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Girish et al [19,20] have studied the graphite particles reinforced Zn matrix composites and found that the hardness and strength were enhanced. However, they found it was difficult to form good interfacial bonding in metal matrix composite due to the large physical and chemical differences between the matrix and the reinforcing phase [21][22][23][24]. This will reduce the load transfer capacity of the enhancement phase [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%